KINDERGARTEN-AGE QUALITY OF LIFE OUTCOMES AFTER LIVER TRANSPLANTATION AT <6 YEARS. (18th May 2018) - Wong, Kerry; Joffe, Ari R; Yap, Jason; Acton, Bryan; Dinu, Irina; Moez, Elham Khodayari; Robertson, Charlene MT
Abstract: BACKGROUND: Given the improved mortality after paediatric liver transplantation, health related quality of life (HRQL) is an important outcome measure and provides valuable information for families. OBJECTIVES: To determine the HRQL of kindergarten-age children who have undergone liver transplantation at age <6 years old. DESIGN/METHODS: Between 1999–2014, all paediatric liver transplant recipients at our center were enrolled in this ethics board approved, longitudinal inception-cohort study. Following informed consent, HRQL was measured using the parent completed Pediatric Quality of Life Inventory, version 4.0 (PedsQL). The association between pre-transplant, transplant, and post-transplant variables and HRQL was examined using multiple regression analyses. Scores were compared to normative scores for HRQL in 8700 children [total PedsQL 82.2 (15.5), psychosocial summary 81.2 (15.3), and physical summary 84.0 (19.7)] and to scores for 130 children with surgical congenital heart disease from early infancy [81.1 (13.9), 77.5 (16.4), and 86.4 (15.3) respectively]. RESULTS: 78 liver transplants for children <6 years of age were performed; 69 patients (88.5%) survived, and all (100%) were assessed at 55.4 (7.2) months of age: 38 with biliary atresia, 11 with acute liver failure, 11 with cholestasis, and 9 with metabolic disease. The mean total PedsQL was 75.6 (SD=15.6), psychosocial summary 72 (15.9) [a composite of emotional functioning 73.8 (16.4), social functioning 74.6 (19.2), and school functioning 70.6 (19.1)], and physical summary 78.2 (20.9). These composite scores were all statistically significantly different from population norms (p<0.001, <0.001, 0.026 respectively) and surgical congenital heart disease patients (p=0.015, 0.029, 0.005). The proportion having a score >1 (expected 15.9%) and >2 (expected 2.27%) SD below population norms were: total PedsQL 20.6% and 11.8%, psychosocial summary 32.3% and 11.3%, and physical summary 19.1% and 7.4%. Having a wait-list status 1 on the Canadian System of Classification was associated with higher total PedsQL (Effect size 9, 95%CI 2, 16; p=0.018) and physical summary (Effect size 15, 95%CI 16, 79; p=.004). None of the perioperative variables were predictive for psychosocial summary. Variables not associated with PedsQL included metabolic disease, PELD score, growth failure, any post-operative severe complication, age at transplant, weight at transplant, socioeconomic status, and year of transplant. CONCLUSION: HRQL after liver transplantation is lower than population norms and congenital heart disease patients. More research is needed to determine why HRQL is low in order to improve the lives of these children.